Possible electron doping of geometrically perfect spin-1/2 kagome-lattice barlowite by reduced graphene oxide - Gupta, Kriti; Ninawe, Pranay; Jain, Anil; Dadwal, Arun; Anas, M.; Malik, V. K.; Yusuf, S. M.; Joy, Pattayil A.; Ballav, Nirmalya (Physical Review B, 2021)
Doping of quantum spin liquid (QSL) insulators by electron or hole leads to intriguing phase transitions to metallic and superconducting states. The barlowite family with geometrically perfect S = 1/2 kagome planes and tunable interkagome coupling is an emerging platform to realize spin-ordered, valence bond crystal, QSL states. Theoretical investigations on electron doping revealed localized states in the band gap of barlowite unlike metallicity in cuprate (Nd2CuO4). We present successful anchoring of phase-pure barlowite crystallites onto reduced graphene oxide (rGO). The resulting barlowite-rGO system was found to be an electrical semiconductor with Arrhenius activation energy of 0.07 eV. Semiconducting properties of the barlowite-rGO system were further modulated with retention of structural integrity. We have attributed such a transformation of electrical transport response to plausible electron doping thereby making charge-doping experiments on barlowite and its analogs propitious.